El derecho a que se considere carga familiar a la mujer embarazada y su incidencia en la rebaja de alimentos - Segovia Barreiro, Anthony Brian (2022)
The Childhood and Adolescence Code regulates the right of the pregnant woman to receive food, which subsists 12 months after the child is born, the main difference with the right to food is that prenatal help meets the needs of the mother such as health, housing, food, etc; As the right to food, it meets the needs of children and adolescents who are holders of this fundamental right, but not the needs of the mother. Due to these considerations, in this research it is made clear that in reality food processes can occur in which alimony could be doubled with respect to a single child; the first pension the mother would receive is prenatal help; And, at the same time, you can also request alimony in another judicial process, which would generate two pensions for the same child during the first 12 months of life, which could violate the economic rights of the obligor, specially when the father or the mother, does not have a stable economic situation, due to lack of sources of employment, among other causes. To comply with the objectives of the work, a field investigation was carried out, with which information was obtained that allowed to conclude that reforms should be made to the Code of Childhood and Adolescence so that the pregnant woman can be considered as a family burden for purposes of the fixation of alimony, guaranteeing in this way the rights of the obligors, without leaving children and adolescents unprotected.